The relationship between corporate governance and financial performance in Сhinese logistics-related listed companies - Pasko, Oleh; Chen, Fuli; Yao, Xuefeng (Management and Entrepreneurship: Trends of Development, 2020)
The purpose of this study is to examine the relationship between corporate governance and financial performance of Chinese logistics-related listed companies. Methodology：We use Stata 16.0 as a data analysis tool, using panel data of 53 listed companies from 2013 to 2019 for analysis. In the multiple regression analysis, ROA is the dependent variable, the six corporate governance factors related to the ownership structure, board of directors, and governance structure are independent variables, and the company size, asset-liability ratio, and market-to-book ratio are control variables. Subsequently, we used ROE instead of ROA to conduct a test, which verified the robustness of the analysis results. Findings: The results show that management ownership, institutional ownership and proportion of the largest shareholder are significantly positively correlated with performance. There is a non-linear relationship between board size and financial performance, while there is no significant relationship between the proportion of independent directors and financial performance. In large companies, CEO duality is significantly negatively correlated with financial performance. Originality/value: Previous research generally used a certain industry as the research object for analysis, and seldom had cross-industry analysis. This research uses listed companies in the entire logistics industry chain as the research object. The research results should also be applicable to listed companies in the logistics industry in other countries. JEL Classification: G34, R41